“Enhancing Artistic Perception in Higher Education through Interactive Multimedia in Fine Arts Courses” - Kodirov Obid Esonboy o‘g‘li (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
Abstract: This article explores the scientific and methodological foundations of using interactive multimedia to enhance artistic perception in fine arts courses at higher education institutions. The study examines how digital tools, virtual galleries, and multimedia resources can develop students’ aesthetic literacy, creative thinking, and critical analysis skills. It also discusses pedagogical strategies for integrating multimedia effectively into lessons to increase engagement, promote independent learning, and foster a deeper understanding of artworks.